Welcome and Keynote Address: The Power of Academic Integrity Communities - Lancaster, Thomas (Canadian Perspectives on Academic Integrity, 2021)
Video presentation can be viewed at https://media.tru.ca/playlist/dedicated/0_0u3o63xd/0_ngpid8xr